Hollow Fe/Ni–CoTe@NCFs nanoarchitecture derived from MOF@MOF as high-efficiency electrocatalysts for boosting oxygen evolution reaction. (18th November 2021) - Li, Wenjin; Chen, Jinpeng; Zhang, Yan; Gong, Weiming; Sun, Mengmeng; Wang, Yanying; Wang, Xianxiang; Rao, Hanbing; Ye, Jianshan; Lu, Zhiwei
Abstract: To improve the oxygen evolution reaction (OER) catalytic efficiency of non-noble-metal-based catalysts, researchers have made great endeavors to adjust the compositions, morphologies and configuration of material. In this work, a dual-metal-organic frameworks (MOFs)-assisted fabrication hierarchical and hollow N-doped carbon nanoframes (NCFs) decorated with Fe/Ni-codoped CoTe nanocomposite catalyst (Fe/Ni–CoTe@NCFs) is reported. Starting from MOF-in-MOF composite precursors, the design and fabrication of Fe/Ni–CoTe by the strategies: i.e, hydrothermal precipitation, chemical etching and low-temperature tellurization, and high-temperature pyrolysis steps. Newly designed catalyst (Fe/Ni–CoTe@NCFs) performs superior OER catalytic activity to afford 10 mA cm −2 at the overpotential of 287 mV with a small Tafel slope of 52.3 mV dec −1 . The frame-like hollow core-shell nanostructures with ample channels into the internal volume and high double-layer capacitance provide the large catalytic active surface area and increase more actives sites. The cooperative effects between alloy and metal telluride, as well as hollow carbon shell promote the activity of OER. Therefore, this study offers a catalyst with great potential for OER and provides the possibility for the application of transition metal tellurides in electrocatalysis. Highlights: A top-down strategy for fabrication of Fe/Ni-codoped CoTe electrocatalyst for OER. Fe/Ni–CoTe decorated hollow N-doped carbon frameworks based on dual-MOFs-assisted fabrication process. Catalyst possess large specific surface area and high nitrogen content. Fe/Ni–CoTe@NCFs catalyst exhibited excellent OER activity y in alkaline media.